ENGLISH FOR SPECIFIC PURPOSES IN MEDICINE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
English is a global language for science, technology, business, and medicine. Its widespread use fosters cross-cultural communication and international cooperation, facilitating the exchange of ideas, research, and medical innovations. Being proficient in English is crucial for professionals across all disciplines, including medicine, to remain competitive and informed in a rapidly evolving global landscape.